The Influence of Financial Literacy and Risk Perception on Investment Intention with Trust as a Mediating Variable: A Study of Generation Z Students Using the Bibit Application - Caecilia Sheryl Kusuma; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study investigates The Influence of Financial Literacy and Risk Perception on Investment Intention, with Trust as a Mediating Variable, among Generation Z students using the Bibit application. The study uses a quantitative methodology with SmartPLS 4.0 analysis and structural equation modeling (SEM). 114 individuals provided information using a standardized questionnaire. The results show that financial literacy significantly and favorably affects investing intention as well as trust. Although risk perception has a beneficial impact on trust, it has no direct effect on investment intention. Interestingly, trust has a large negative impact on investment intention, suggesting a complicated mediating role. The behavioral dynamics of Generation Z in fintech-based investing platforms are highlighted in this study, which adds to the body of literature on digital investments